2011
DOI: 10.1007/s10600-011-0079-y
|View full text |Cite
|
Sign up to set email alerts
|

Chemical constituents from the roots of Cephalaria kotschyi

Abstract: Cephalaria kotschyi Boiss. et Hoh. (Dipsacaceae) is an endemic plant of the Caucasus region growing in Azerbaijan. Earlier phytochemical studies reported the isolation of triterpene saponins, flavonoids, and gentianine type alkaloids from the roots and flowers of C. kotschyi [1][2][3][4][5][6][7]. In our previous study we described the isolation of the iridoid glycosides loganin and gentiopicroside from the roots of this plant [8].Herein we report, together with the gentiopicroside and loganin described previ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Compounds 3 and 4 showed deprotonated ion as m / z = 375 with UV-Vis maximum at 231 nm. Based on comparison with chemical standard compound 3 was identified as loganic acid, which was previously confirmed in Cephalaria kotshyi [ 46 ]. Compound 4 was described as loganic acid isomer due to the same molecular weight and identical fragmentation pattern ( Table 1 ).…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…Compounds 3 and 4 showed deprotonated ion as m / z = 375 with UV-Vis maximum at 231 nm. Based on comparison with chemical standard compound 3 was identified as loganic acid, which was previously confirmed in Cephalaria kotshyi [ 46 ]. Compound 4 was described as loganic acid isomer due to the same molecular weight and identical fragmentation pattern ( Table 1 ).…”
Section: Resultsmentioning
confidence: 88%
“…After the comparison with chemical standard, 15 was identified as loganin. Loganin was previously confirmed in Cephalaria elaziginesis , Cephalaria kotschyi and Cephalaria isaurica [ 27 , 46 , 48 ]. Compounds 8 , 16 – 20 and 29 were tentatively classified as other iridoids based on UV-Vis maxima observed at ca.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…This wide range of usages has led to investigations on different Cephalaria species. Many chemical identification studies have been reported that this genus contains triterpenoid saponins, flavonoids, alkaloids, furofuranic lignans and iridoids [5][6][7][8][9][10][11][12][13]. According to these literatures, it is also known that these compounds have different activities including antimicrobial, hemolytic, hypolipidemic, immunomodulating and cytotoxic [7-8, 11-12, 14].…”
Section: Introductionmentioning
confidence: 99%